La persecución religiosa en el siglo XXI - César Castilla Villanueva (Ius Humani. Jornal do direito, 2017)
All kind of persecutions are deplorable acts, especially those targeting religious groups, because it limits the freedom of the human being in his relationship with God. Unfortunately, the universal history shows us that religious persecutions have been originated since ancient times. Until now, nothing has been done to prevent it. The present essay applies an historical-sociological approach related to the field of the political sciences to be able to explain the causes of the persecutions privileging the study of the social environment. As empirical evidence have been chosen cases of the Armenian’s genocide late and early nineteenth and twentieth century, and also the case of the religious persecution towards the Izadi population by the terrorist group “Islamic State” (Daesh). Finally, this paper doesn’t aim to find solutions but invites to reflection, resuming intercultural dialogue proposed by the Austrian Hans Köchler and Iranian President Mohammad Khatami during the twentieth century, as an option to develop tolerance and promote understanding between different cultures in order to work together and prevent further cases of persecution in XXI century.